Markers of Inflammation Associated with Plaque Progression and Instability in Patients with Carotid Atherosclerosis - Enrico Ammirati; Francesco Moroni; Giuseppe Danilo Norata; Marco Magnoni; Paolo G. Camici (Mediators of Inflammation)
Atherosclerosis is the focal expression of a systemic disease affecting medium- and large-sized arteries, in which traditional cardiovascular risk factor and immune factors play a key role. It is well accepted that circulating biomarkers, including C-reactive protein and interleukin-6, reliably predict major cardiovascular events, including myocardial infarction or death. However, the relevance of biomarkers of systemic inflammation to atherosclerosis progression in the carotid artery is less established. The large majority of clinical studies focused on the association between biomarkers and subclinical atherosclerosis, that is, carotid intima-media thickening (cIMT), which represents an earlier stage of the disease. The aim of this work is to review inflammatory biomarkers that were associated with a higher atherosclerotic burden, a faster disease progression, and features of plaque instability, such as inflammation or neovascularization, in patients with carotid atherosclerotic plaque, which represents an advanced stage of disease compared with cIMT. The association of biomarkers with the occurrence of cerebrovascular events, secondary to carotid plaque rupture, will also be presented. Currently, the degree of carotid artery stenosis is used to predict the risk of future cerebrovascular events in patients affected by carotid atherosclerosis. However, this strategy appears suboptimal. The identification of suitable biomarkers could provide a useful adjunctive criterion to ensure better risk stratification and optimize management.